2015
DOI: 10.1177/0015732515572055
|View full text |Cite
|
Sign up to set email alerts
|

Foreign Direct Investment, Trade Openness and Economic Growth

Abstract: In recent years, the Thailand economy has become more open to foreign trade as well as foreign direct investment (FDI). Thus, the main objective of this article is to examine whether FDI and international trade have positively contributed to the economic growth of Thailand. The results of the Granger causality tests indicate that they are indeed important determinants of growth in Thailand. This suggests that policymakers in Thailand should liberalize its economy to encourage foreign trade and FDI inflows to a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
17
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 35 publications
(24 citation statements)
references
References 20 publications
6
17
0
Order By: Relevance
“…This shows that their impact on economic growth is minimal. Our results corroborate that of other studies such as Akinlo (2004), Sapsford (1996, 1999), Yusoff and Nuh (2015), and Alfaro et al (2004Alfaro et al ( , 2006Alfaro et al ( , 2010. These results also support the findings in the study of Shaikh (2010) where 47 developing countries were examined between 1981 and 1999 using the OLS regressions method, and a positive relationship between FDI and the manufacturing sector was discovered.…”
Section: Tansupporting
confidence: 92%
“…This shows that their impact on economic growth is minimal. Our results corroborate that of other studies such as Akinlo (2004), Sapsford (1996, 1999), Yusoff and Nuh (2015), and Alfaro et al (2004Alfaro et al ( , 2006Alfaro et al ( , 2010. These results also support the findings in the study of Shaikh (2010) where 47 developing countries were examined between 1981 and 1999 using the OLS regressions method, and a positive relationship between FDI and the manufacturing sector was discovered.…”
Section: Tansupporting
confidence: 92%
“…The nexus between trade openness and economic growth has attracted significant interest in the literature. Recent studies have investigated both regional and individual country experiences, incorporating other institutional, social, economic, and technological factors (see Dowrick and Golley, 2004;Yanikkaya, 2003;Awokuse, 2008;Shahbaz, 2012;Menyah et al, 2014;Olubiyi, 2014;Sakyi et al, 2015aSakyi et al, , 2015bYusoff & Nuh, 2015;Ee, 2016;Salahuddin & Gow, 2016;Zahonogo, 2016;Khamphengvong et al, 2017;Mireku et al, 2017;Keho & Grace Wang, 2017;Pradhan et al, 2017;Darku & Yeboah, 2018;IDRIS et al, 2018;Huchet-Bourdon et al, 2018;Benita, 2019;Burange et al, 2019;Ma et al, 2019;Tang et al, 2019;Duodu et al, 2020;Nwadike et al, 2020).…”
Section: A Brief Literature Reviewmentioning
confidence: 99%
“…Similarly, Yusoff and Nuh (2015) investigated the determinants of Thailand's economic growth using the Granger causality tests. They found that there was an establishing link between international trade and economic growth.…”
Section: Literature Reviewmentioning
confidence: 99%